Influence of Absorption cross section of saturable absorber on Passive Q-switching laser pulse characteristics - Abdul-Kareem M. Salih (University of Thi-Qar Journal of Science, 2019)
The absorption cross section of saturable absorber influence on passive Q-switching laser pulse behavior has beenstudied by numerical solution of rate equations mathematical model. We report the passive Q-switching of the2 44 Cr : BeAl O  (alexandrite) laser with the yttrium silicate 2 54 Cr :Y SiO  (Cr :YSO) solid state saturable absorber.The study shows that the behavior pulse energy, initial value of population inversion, and the laser photon number isscaling up when the ground state absorption cross section of saturable absorber increasing, while the behavior of pulseduration is scaling down.